Developing final year project management system running on android apps / Mohamad Syazwan Musa - Musa, Mohamad Syazwan (2015)
The aims of this project is to manage the activity of Final Year Project course by developing a Final Year Project Management System which is running on android apps. The apps help the supervisor to monitor and evaluate their students work progress. It also help the students to communicate and send report progress to supervisor thus this apps make the Final Year Project become convenient and easy. This apps was developed by using Android Studio, Parse.com and Sinch.com. The android studio arc Java base language were develop by google and it is an open source mobile operating system. The Parsc.com is a hosted service, providing backend service for android platform act as a database. While Sinch.com was used to support the Parsc.com for capability to make calling and messaging apps for free. This apps provide several menu which users can send report, view report, calling, messaging, email, view students profile and many others which will be explain further more throughout this paper.